2015
DOI: 10.3329/bjp.v10i4.25160
|View full text |Cite
|
Sign up to set email alerts
|

Uricosuric activity of <i>Tinospora cordifolia</i>

Abstract: <p class="Abstract">Uricosuric activity of different extracts of <em>Tinospora cordifolia</em> was studied in hyperuricemia induced in albino Wistar rat using potassium oxonate. The uric acid level in serum and urine were measured.  Uricosuric activity was also evaluated using phenol red dye excretion model.  Phenol red levels were measured in blood. In potassium oxonate induced hyperuricemia, probenecid, aqueous, hydro-alcoholic, dichloromethane extract and galo satwa (starch of <em>T.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
(8 reference statements)
1
2
0
1
Order By: Relevance
“…This model was successful in raising the serum uric acid level with a highly significant result as compared to normal control (p-value <0.001) and also slightly raised urinary uric acid level with an increase in fractional excretion of urate that is due to the increase of plasma uric acid level and a greater amount of uric acid filtered in the kidney tubules [25]. These results are comparable to Shah and Shah's study in which a similar model showed the same effect on serum, urinary uric acid level, and its fractional excretion [26].…”
Section: Discussionsupporting
confidence: 71%
“…This model was successful in raising the serum uric acid level with a highly significant result as compared to normal control (p-value <0.001) and also slightly raised urinary uric acid level with an increase in fractional excretion of urate that is due to the increase of plasma uric acid level and a greater amount of uric acid filtered in the kidney tubules [25]. These results are comparable to Shah and Shah's study in which a similar model showed the same effect on serum, urinary uric acid level, and its fractional excretion [26].…”
Section: Discussionsupporting
confidence: 71%
“…Polysaccharides in aqueous extract and Galo satwa may be responsible for uricosuric action. [27] In vitro Xanthine Oxidase Inhibitory (XOI) effect of some medicinal plants namely Apium graveolens (Ajmoda), Azadirachta indica (Nimba), Catharanthus roseus (Sadabahar), Citrus limon (Nimbu), Cymbopogon citratus (Nimbu Bheda), Nyctanthus arbour-tristis (Parijata), Psidium guajava (Amrooda), Salvia hispanica (Chia), Tinospora cordifolia (Guduchi) and Trigonella foenum-graecum (Meethi), was measured spectrophotometrically. Allopurinol has been used as a positive control in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found that stem extracts of Tinospora cordifolia can decrease UA levels in rats with hyperuricemia. The main components of the purified extract are flavonoids containing flavone-o-glucoside, including apigenin, luteolin, morin and routine (Shah and Shah, 2015). Flavonoids can also decrease UA levels by increasing uricase activity to improve the decomposition and excretion of UA (Kuo et al , 2012).…”
Section: Discussionmentioning
confidence: 99%